Visual Communication Design Analysis of the Instagram Account @SOHIB.QURAN - Yusyrifah Halid; Fitri Nur Fajrin (Palakka : Media and Islamic Communication, 2023)
This study aims to determine the meaning of visual communication design elements of typography, illustrations and colors on the poster of the Instagram account @sohib.quran. The method used in this research is qualitative method. The results of the study found that the elements contained in the accountsinstagram @sohib.quran between typographic elements, illustrations, colors are interrelated so that they can obtain a meaning. 1) TypographyHeadline made bigger and more prominent than the others as a sign indicating the main discussion in the poster, then forbody text placed belowheadline as an explanation of the poster which consists of the hadiths of the Prophet and Fatwas from prominent Islamic scholars, in addition to that the @sohib.quran account also includes sources of fatwas or hadiths in the poster, the placement is underbody text. (2) The use of illustrations in the @sohib.quran account poster is made according to the background context of the message conveyed in the poster. (3) the use of the color of the @sohib.quran poster uses neutral colors such as gray which are softer and can match other colors.